2023
DOI: 10.13057/biodiv/d240539
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and characterization of arrowroot (Maranta arundinacea) tuber yogurt

SITARESMI YUNINGTYAS,
ANNA PRIANGANI ROSWIEM,
DINA AZAHRA
et al.

Abstract: Abstract. Yuningtyas S, Roswiem AP, Azahra D, Alfarabi M. 2023. Antioxidant activity and characterization of arrowroot (Maranta arundinacea) tuber yogurt. Biodiversitas 24: 2850-2854. The main benefit of yogurt is its ability to improve the digestive health tract by enhancing the condition of the intestinal flora and its environment. Nowadays, adding natural ingredients to yogurt is a widely practiced trend towards further increasing its efficacy as a healthy drink. Arrowroot tuber (Maranta arundinacea L.) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
8

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 31 publications
0
1
0
8
Order By: Relevance
“…Ararot rizomlarının kimyasal içeriği ile ilgili birçok çalışma literatürde yer almakla birlikte; içeriğin kullanılan ekstraksiyon yöntemi, bitkinin orijini, yaşı, çevresel faktörler gibi etkenlere bağlı olarak değiştiği bildirilmiştir [8]. Literatür taramalarına göre ararot rizomlarının farklı polaritedeki (petroleteri, kloroform, etilasetat, metanol, su ve etanol) ekstreleri alkaloitler, karbonhidratlar, kardiyak glikozitler, proteinler, amino asitler, terpenler, saponinler [3,10,12,13,18,24,32], flavonoitler [10,13,16,18], reçineler [33], tanenler [16], zamk [10,16,18], lignin, antrakinonlar [34] ve steroller [3,10,13,18] içerir. Nishaa ve arkadaşları (2013) ararot rizomlarının petol eteri, kloroform, etil asetat ve etanol ekstrelerini incelemiş ve etanol ekstresinde taranan bileşik gruplarının tamamının bulunduğunu bildirmiştir (Tablo 1).…”
Section: Kimyasal İçerikunclassified
See 3 more Smart Citations
“…Ararot rizomlarının kimyasal içeriği ile ilgili birçok çalışma literatürde yer almakla birlikte; içeriğin kullanılan ekstraksiyon yöntemi, bitkinin orijini, yaşı, çevresel faktörler gibi etkenlere bağlı olarak değiştiği bildirilmiştir [8]. Literatür taramalarına göre ararot rizomlarının farklı polaritedeki (petroleteri, kloroform, etilasetat, metanol, su ve etanol) ekstreleri alkaloitler, karbonhidratlar, kardiyak glikozitler, proteinler, amino asitler, terpenler, saponinler [3,10,12,13,18,24,32], flavonoitler [10,13,16,18], reçineler [33], tanenler [16], zamk [10,16,18], lignin, antrakinonlar [34] ve steroller [3,10,13,18] içerir. Nishaa ve arkadaşları (2013) ararot rizomlarının petol eteri, kloroform, etil asetat ve etanol ekstrelerini incelemiş ve etanol ekstresinde taranan bileşik gruplarının tamamının bulunduğunu bildirmiştir (Tablo 1).…”
Section: Kimyasal İçerikunclassified
“…Rizomların ve rizomlardan elde edilen ürünlerin antimikrobiyal etkinliği birçok mikrobiyal suşa (Staphylococcus aureus [16,52], Staphylococcus epidermidis [16], Escherichia coli [16,53], Clostridium perfringens [53], Streptococcus mutans, Salmonella sp., Bacillus cereus [16], Lactobacillus sp. [16,53,54] (L. acidophilus [13,55], L. plantarum [34], L. casei [16] (rhamnosus ve shirota suşları)), Bifidobacterium bifidum, Bifidobacterium longum [16]) karşı test edilmiş ve etkili bulunmuştur. Rizomların Tinea Pedis'i tedavi etme etkisi antifungal aktivitesine bağlanmıştır [26].…”
Section: Antimikrobiyal Ve Prebiyotik Etkiunclassified
See 2 more Smart Citations
“…It was determined that the antimicrobial activities as well as qualities of dairy products (yogurt, cheese, and butter) were improved by adding essential oils and extracts of herbs and spices [ 66 ]. Yuningtyas et al [ 67 ] reported that yogurts with arrowroot ( Maranta arundinacea ) added both contain higher lactic acid bacteria and have higher antioxidant activity. Shirani et al [ 68 ] also mentioned that Echinops setifer extracts improve yogurt quality and functionality by containing natural bioactive sources.…”
Section: Application Of Natural Antimicrobialsmentioning
confidence: 99%